John Prentiss Poe, The Baltimore City Code, Containing the Public Local Laws of Maryland Relating to the City of Baltimore, and the Ordinances of the Mayor and City Council, in Force on the First Day of November, 1891, With a Supplement, Containing the Public Local Laws Relating to the City of Baltimore, Passed at the Session of 1892 of the General Assembly, and Also the Ordinances of the Mayor and City Council, Passed at the Session of 1891–92, and of 1892–1893, Up To the Summer Recess of 1893 522–23 (Vol. 1, 1888), § 742 - (:unkn) unknown (General Publisher, 1888)
Prohibited the carrying of a pistol, dirk knife, Bowie knife, slingshot, billy, brass, iron or any other metal knuckles, razor, or any other deadly weapon if arrested for being drunk and disorderly. Punishable by fine of $5-25, and confiscation of the weapon.
--
Keywords: POSSESSION - DANGEROUS PERSONS